Mediation as a suitable dispute resolution method in medical negligence cases: special reference to the Malaysian position - Ambaras Khan, Hanna; Bastiampillai, Andriea; Mon, Su Wai (University Putra Malaysia Press, 2020)
Medical negligence is an act or omission by a medical professional that departs from the accepted medical standard of care. Currently, medical negligence claims fall under the law of tort adversarial system. The objective of this paper is to study the practice of mediation as a dispute resolution for medical negligence cases in Singapore and the United Kingdom and thereafter, make a recommendation of the application of mediation as an alternative to litigation in resolving medical negligence cases in Malaysia. Mediation offers positive benefits, amicable dispute settlements, and speedy process to affected parties. Further, it may overcome the challenges faced by the parties in litigation, such as a lengthy period in pursuing claims. This paper adopted both quantitative and qualitative research methods. The former involves library research and interviews, and the latter is in the form of survey questionnaires using a structured questionnaire. The results showed that >80% of the respondents agreed that mediation was a suitable dispute resolution method and should be applied in medical negligence. Mediation resolves the dispute and preserves the trust in the doctor-patient relationship. It is hoped that Malaysia will offer mediation as either a separate dispute resolution method for medical negligence cases or mediation to be offered under the current court-annexed system with a modification whereby the parties may opt for mediation at any time upon registration of the case without the need to wait for pretrial case management stage.